Diagnosing Mechanisms of Ocean Carbon Export in a Satellite-Based Food Web Model - Bisson, Kelsey; Siegel, David A.; DeVries, Timothy (Frontiers in Marine Science, 2020)
The net primary productivity (NPP) of marine phytoplankton is ~ 50 Pg C yr-1, and roughly 10-20% of this NPP is exported out of the surface ocean as sinking particulate organic carbon (POC). Numerous mechanisms are hypothesized to control POC export out of the surface ocean but the relative importance of the various mechanisms remains poorly quantified on global scales. Here, we use a previously published satellite-based mechanistic model of POC export to examine the effects on global POC export of size-specific physical aggregation, size-specific and temperature-dependent zooplankton fecal pellet production, and size-specific and temperature-dependent non-grazing phytoplankton mortality. We test these mechanisms in different model configurations to determine if these processes improve the ability of the model to match POC export observations, and to assess the role of each process in controlling global POC export. We find that all model configurations predict that over 60% of the global POC export is from small zooplankton fecal pellets. All model configurations predict similar total POC export, and we find only small differences in the magnitude, timing, and geographical variations of total POC export. However, the fraction of total POC export due to sinking phytoplankton aggregates, and that due to the fecal pellets of large zooplankton, vary by more than a factor of two across the different model configurations. The POC export in all models is most sensitive to parameters controlling zooplankton fecal fluxes and non-grazing phytoplankton mortality. We compared zooplankton grazing rates predicted by the models to results of experimental data, and found that some models match the experimental grazing rates better than others, although data uncertainties remain large. More field measurements of bulk ecosystem rates (i.e., phytoplankton aggregation and zooplankton grazing), as well as explicit determinations of of the proportion of fecal matter to phytoplankton aggregation, will help to better constrain mechanistic models of global POC export.